Alström syndrome—wide clinical variability within the same variant: a case report and literature review - Jecan-Toader, Diana; Trifa, Adrian; Lucian, Bogdan; Pop, Tudor Lucian; Cainap, Simona Sorana (Frontiers in Pediatrics, 2024)
Background: Alström disease is a rare disorder caused by various variants in the ALMS1 gene. It is characterised by multiorgan involvement, namely neurosensory deficits, endocrine and metabolic disturbances, cardiomyopathy, and hepatic and renal dysfunction. The disease exhibits marked interindividual variability, both in clinical manifestations and age of onset. Several attempts have been made to establish a relationship between phenotype and genotype, with little success.We present the case of an infant who presented with dilated cardiomyopathy, aboveaverage weight and neurosensory deficits, raising the suspicion for Alström syndrome, later confirmed through genetic testing. Moreover, we conducted an extensive literature search to identify all reported cases having the same variant as our patient, in order to evaluate whether specific mutated alleles have a role in determining phenotype-genotype associations.Results: A 4-month-old female infant with a recent history of bronchiolitis was referred to our centre due to a systolic murmur. In our service, the clinical exam was significant for above-average weight, dyspnea, wheezing and a grade II systolic murmur. Echocardiography revealed dilated cardiomyopathy with severe systolic dysfunction of the left ventricle. Laboratory investigations revealed elevated NT-proBNP and troponin levels, along with positive IgM antibodies for CMV and EBV. Dilated cardiomyopathy attributed to viral myocarditis was suspected. Treatment with ACE inhibitors and diuretics was started, with a favourable response initially. However, after a few months, the patient presented with vertical nystagmus and head bobbing. The ophthalmologic exam revealed cone-rode dystrophy. Considering the constellation of symptoms, Alström syndrome was suspected. Genetic testing revealed a homozygous variant (c.4156dup (p.Thr1386Asnfs*15)) in the ALMS1 gene, confirming the diagnosis.Our literature review revealed 8 additional cases harbouring the same variant as our patient, five in a heterozygous state, two in a homozygous state and one with only one allele identified. The identified patients presented high heterogeneity of clinical manifestations and age of onset. The heterogeneity persisted even in patients with homozygous variants, suggesting the involvement of factors beyond the specific disease-causing variant in determining disease manifestation. Therefore, genotype-phenotype correlations might not be supported by specific variants.